2019
DOI: 10.1177/1059840519846649
|View full text |Cite
|
Sign up to set email alerts
|

Bullying in School: Importance of and Challenges Involved in Talking to the School Nurse

Abstract: Bullying has negative consequences for health and quality of life of students. This study is part of a pilot project, “School Health,” which included a web-based questionnaire completed by students before a consultation with the school nurse. The aim of this study was to explore how students experience answering questions about bullying before an individual consultation and how they talk about bullying with the school nurse. This study had qualitative design with individual and focus group interviews and invol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 21 publications
0
18
0
Order By: Relevance
“…Norwegian students participating in a qualitative study reported that seeking help for bullying was generally difficult, and that if they told a teacher, little or nothing would be done. Other barriers to seeking help were embarrassment, feelings of insecurity, and worries that the bullying might worsen ( 11 ). Help-seeking might not lead to better outcomes in as straightforward a manner as one thinks, especially when it comes to bullying victimization.…”
Section: Introductionmentioning
confidence: 99%
“…Norwegian students participating in a qualitative study reported that seeking help for bullying was generally difficult, and that if they told a teacher, little or nothing would be done. Other barriers to seeking help were embarrassment, feelings of insecurity, and worries that the bullying might worsen ( 11 ). Help-seeking might not lead to better outcomes in as straightforward a manner as one thinks, especially when it comes to bullying victimization.…”
Section: Introductionmentioning
confidence: 99%
“…The overwhelming differences in bullying between genders might be the tip of the iceberg of the problem: bullying and cyberbullying are linked to violence, and the risk of physical and psychological health problems; however, violence prevention requires a more salutogenic view of adolescents’ relationships: while adults seek prevention of violence, adolescents seek interpersonal wellbeing, construction of their gender identity and belonging to a dominant group, meaning bullying and victimization can become normalized and minimized (Mishna et al., 2020). Public health nurses and school nurses have an active role in bullying detection (Kvarme et al., 2020), and violence prevention strategies require a more inclusive orientation to maintain health, with a focus that is not just on violence per se .…”
Section: Discussionmentioning
confidence: 99%
“…School nurses play a major role in identifying, counseling, and protecting the victims of bullying. Kvarme et al (2020) reported that youth experiencing bullying will seek a safe refuge to avoid the bully(s), and that refuge is often the school health office. The school nurse is often viewed by students as a confidant, someone who is outside the academic system and is in a position to help and give guidance.…”
Section: Factors Affecting Mental Healthmentioning
confidence: 99%
“…The school nurse is often viewed by students as a confidant, someone who is outside the academic system and is in a position to help and give guidance. Victims of bullying visited the nurse more frequently and followed the recommendations/advice of the school nurse more often than advice/ recommendations given by other adults (Kvarme et al, 2020). Examples of school nurse interventions, including several important questions the school nurse can ask to determine if a youth's symptoms may be related to bullying, will be provided in our Part 2 article.…”
Section: Bullyingmentioning
confidence: 99%